Hemostasis Systems in the Formation of Destruction in Tuberculosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Infectious inflammation caused by the pathogen triggers the uncontrolled spread of proinflammatory mediators, followed by their activation of macrophages, neutrophils, lymphocytes and a number of other cells.With the development of tuberculosis against the background of pronounced immunodeficiency and the predominance of the exudative nature of inflammation with damage to the microhemocirculatory bed of the lungs, a significant deposition of fibrin in the inflammatory zone becomes possible.